Bronchial ethanol injection therapy for airway obstruction in lung cancer patients. Issue 9 (29th July 2021) - Okabe, Fukuko; Yano, Yukihiro; Kuge, Tomoki; Uenami, Takeshi; Kanazu, Masaki; Mori, Masahide
Abstract: Obstructive endobronchial tumours often cause decreased quality of life. Bronchial ethanol injection (BEI) therapy is considered an effective modality for airway dilatation or haemoptysis without specialist equipment. Here, we report experiences of two cases in which BEI therapy was effective for obstructive endobronchial tumours. In Case 1 with adenoid cystic carcinoma of the lung, BEI therapy and balloon dilatation were performed as treatment for the left main bronchus restenosis after metallic stent insertion. In Case 2 with squamous cell carcinoma of the lung, BEI therapy was performed after radiation therapy to the lesion that recurred in the entrance of the superior segment of the right lower lobe. Tumour progression was controlled with multiple BEI therapy. We consider BEI therapy useful because this procedure is easy to conduct, has low cost and can be done under particular conditions including post‐tracheobronchial stent placement and post‐radiation. Abstract : Obstructive endobronchial tumours often cause decreased quality of life. Bronchial ethanol injection (BEI) therapy is considered an effective modality for airway dilatation or haemoptysis without specialist equipment. Here, we report experiences of two cases in which BEI therapy was effective for obstructive endobronchial tumours.